2015
DOI: 10.1200/jco.2015.33.7_suppl.94
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of manual and automated rectal contours using helical tomotherapy image guidance scans during prostate radiotherapy.

Abstract: 94 Background: Prostate radiotherapy can be delivered using daily image-guided helical tomotherapy. Previous work has shown that contouring the rectum on the kV planning CT scan has a Jaccard conformity index (JCI) of 0.78 for different oncologists (inter-observer variability) and 0.82 for a single oncologist (intra-observer variability) (Lutgendorf-Caucig C et al. Feasibility of CBCT-based target and normal structure delineation in prostate cancer radiotherapy: multi-observer and image multi-modality study. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…We have previously investigated interobserver contouring of this part of the rectum using deliberately extended image guidance scans. 59 We found that median Jaccard conformity index above the superior pelvic muscles was 0.84, interquartile range (IQR) 0.80–0.87. The corresponding value below the muscles was 0.62, IQR 0.53–0.72.…”
Section: Discussionmentioning
confidence: 80%
“…We have previously investigated interobserver contouring of this part of the rectum using deliberately extended image guidance scans. 59 We found that median Jaccard conformity index above the superior pelvic muscles was 0.84, interquartile range (IQR) 0.80–0.87. The corresponding value below the muscles was 0.62, IQR 0.53–0.72.…”
Section: Discussionmentioning
confidence: 80%
“…For daily MVCT scans, the rectum was identified using a locally developed autosegmentation system based on the Chan-Vese algorithm [32]. Manual contouring of the 4174 MVCT scans (over 62,000 slices) in this study would not have been practicable, and the autosegmentation system has previously been shown to fall within an acceptable range for intra-and inter-observer variability [33]. Dose was calculated directly from the MVCT images (and recalculated for kVCT images) using CheckTomo, an independent ray-tracing dose calculation algorithm [34,35].…”
Section: Voxtox Study Design and Patient Informationmentioning
confidence: 99%
“…[26,35,11,39,26,48,49,58,5] and references therein. Moreover, various applications were put forward for instance in optical flow [19], tomographic imaging [3], and medical imaging [59,14,15,12,51,20].…”
mentioning
confidence: 99%